2015
DOI: 10.1111/1744-9987.12344
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Levels in Acute Liver Failure Patients Treated with Plasma Filtration with Dialysis and Plasma Exchange

Abstract: Plasma filtration with dialysis (PDF) is a blood purification therapy in which simple plasma exchange (PE) is performed using a selective membrane plasma separator while the dialysate flows outside of the hollow fibers. Improvement of hypoadiponectinemia is considered to be a useful therapeutic approach for ameliorating fatal conditions including cardio-metabolic and infectious disease. We investigated the effects of PDF in comparison to PE in terms of plasma adiponectin (APN) changes in patients with acute li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In addition, previous reports have shown that PDF increases adiponectin levels in patients with liver failure; thus, it may be useful as a treatment for patients with liver failure. 12 In this case, PDF showed a remarkable effect, due to which we can surmise that substances within the treatment target of PDF may be the cause of CLS. PDF may ameliorate capillary leaks.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, previous reports have shown that PDF increases adiponectin levels in patients with liver failure; thus, it may be useful as a treatment for patients with liver failure. 12 In this case, PDF showed a remarkable effect, due to which we can surmise that substances within the treatment target of PDF may be the cause of CLS. PDF may ameliorate capillary leaks.…”
Section: Discussionmentioning
confidence: 65%
“…Reducing the use of FFP can lower the cost of treatment and reduce the risk of blood transfusion complications. In addition, previous reports have shown that PDF increases adiponectin levels in patients with liver failure; thus, it may be useful as a treatment for patients with liver failure 12 …”
Section: Discussionmentioning
confidence: 98%
“…Plasma filtration with dialysis (PDF) is a blood purification therapy in which sPE is performed while the dialysate flows outside of the hollow fibers. We have previously reported that plasma adiponectin levels increased significantly after PDF, but decreased after conventional PE . Adiponectin exerts potent anti‐inflammatory effects, as documented by a reduction in inflammatory mediators .…”
Section: Discussionmentioning
confidence: 93%
“…cPED is a new blood purification method that simplifies plasma diafiltration (PDF), which utilizes a selective membrane plasma separator to perform PE while the dialysate is pumped outside the hollow fiber [8]. PDF has already been used for acute liver failure [11][12][13]. Continuous PDF, in which PDF is performed at a slower place in hemodynamically unstable patients, is used clinically [14].…”
Section: Discussionmentioning
confidence: 99%